Pelatihan Dental Health Education Tentang Kewaspadaan Penularan Covid-19 Pada Kader Meunasah Manyet - Reca, Reca; Salfiyadi, Teuku; Willis, Ratna; Rimadeni, Yeni; Liana, Intan; Andriani, Andriani; Feriana Putri, Citra (Poltekkes Kemenkes Aceh, 2024)
Health cadres as the spearhead of society need to equip themselves with knowledge and help efforts to improve the optimal level of dental and oral health. Therefore, cadres must master various skills and knowledge techniques. In this activity, training is carried out with the hope that cadres can transfer the knowledge received to be conveyed back to the community, especially in high risk groups for dental and oral diseases. This community service aims to carry out dental health education training in increasing readiness and vigilance for the transmission of COVID-19 in Gampong Meunasah Manyet cadres, Aceh Besar District. This community service is carried out using a quantitative method with a descriptive approach, with a target of 40 posyandu cadres. The intervention provided was in the form of cadre training. The results of the evaluation of the attendance of participants, 100% attended the training well and were active. The results of community service in Gampong Meunasah Manyet, Aceh Besar District, obtained the results of cadre knowledge after being given training increased by 75%. It is recommended that puskesmas officers in the working area to provide training to Posyandu cadres at least once every 3 months and on an ongoing basis to further increase the activity of Posyandu cadres.